Advanced Routes of Biological and Bio-electrocatalytic Carbon Dioxide (CO2) Mitigation Toward Carbon Neutrality - Kondaveeti, Sanath; Abu-Reesh, Ibrahim M.; Mohanakrishna, Gunda; Bulut, Metin; Pant, Deepak (Frontiers in Energy Research, 2020)
Changes in the environment due to multiple factors such as combustion of fossil fuels, heating, transportation, deforestation, etc. had led to more greenhouse gases in atmosphere that eventually lead to rise in global temperatures. Carbon dioxide (CO2) is the major factor for rapid rise in global temperature. One of the best encouraging technological advances to address global warming is to transform CO2 into value-added commodities that offer a win-win strategy. In this regard, intensive research has been pursued around the world for development of feasible systems in product recovery or product synthesis from CO2 rich industrial emissions. We envision that biological CO2 reduction or conversion process can be beneficial for developing carbon neutral technologies. The integration of CO2 emitting industrial technologies with CO2 converting biological systems can be helpful in achieving sustainable value-added products with no or minimal loss of energy and materials which is assuring for improved economics. The CO2 converting bioprocesses can be directly integrated with the processes emitting high amount of CO2. This symbiotic integration can make the whole process carbon neutral. Herein, this review highlights an insight on research activities of biological CO2 mitigation using photo catalysts (algae and photo bacteria), anaerobic biocatalyst (bacteria), gas fermentation and enzymatic catalyst. Perspectives and challenges of these technologies have been discussed.